Visibility of liquid embolic agents in fluoroscopy: a systematic in vitro study - Schmitt, Niclas; Wucherpfennig, Lena; Hohenstatt, Sophia; Weyland, Charlotte S.; Sommer, Christof-Matthias; Bendszus, Martin; Möhlenbruch, Markus Alfred; Vollherbst, Dominik (Journal of neuroInterventional surgery, 2023)
Background Endovascular embolization using liquid embolic agents (LEAs) is frequently applied for the treatment of intracranial vascular malformations. Appropriate visibility of LEAs during embolization is essential for visual control and to prevent complications. Since LEAs contain different radiopaque components of varying concentrations, our aim was the systematic assessment of the visibility of the most used LEAs in fluoroscopy. - Methods A specifically designed in vitro model, resembling cerebral vessels, was embolized with Onyx 18, Squid 18, Squid 12, PHIL (precipitating hydrophobic injectable liquid) 25%, PHIL LV (low viscosity) and NBCA (n-butyl cyanoacrylate) mixed with iodized oil (n=3 for each LEA), as well as with contrast medium and saline, both serving as a reference. Fluoroscopic image acquisition was performed in accordance with clinical routine settings. Visibility was graded quantitatively (contrast to noise ratio, CNR) and qualitatively (five-point scale). - Results Overall, all LEAs provided at least acceptable visibility in this in vitro model. Onyx and Squid as well as NBCA mixed with iodized oil were best visible at a comparable level and superior to the formulations of PHIL, which did not differ in quantitative and qualitative analyses (eg, Onyx 18 vs PHIL 25% along the 2.0 mm sector: mean CNR±SD: 3.02±0.42 vs 1.92±0.35; mean score±SD: 5.00±0.00 vs 3.75±0.45; p≤0.001, respectively). - Conclusion In this systematic in vitro study, relevant differences in the fluoroscopic visibility of LEAs in neurointerventional embolization procedures were demonstrated, while all investigated LEAs provided acceptable visibility in our in vitro model.
Published online first 4 May 2022
Gesehen am 12.06.2023